Surgical management of C-type subaxial cervical fractures using cervical traction followed by anterior cervical discectomy and fusion within 12 h after the trauma - Pasquale Donnarumma (Journal of Craniovertebral Junction and Spine, 2017)
Study Design: This was a retrospective cohort study. Objective: To report our 10-year experience of closed reduction using Crutchfield traction followed by anterior cervical discectomy and fusion within 12 h from injury for C-type subaxial cervical fractures (according to the AOSpine classification system). Methods: Clinical records and neuroimaging were retrospectively reviewed. Surgical details were provided. Results: A total of 22 patients were included in the study. The cervical fracture was diagnosed after whole-body computed tomography scan on admission in all cases. Crutchfield traction was applied within 1–5 h from the diagnosis. Surgery consisting of anterior microdiscectomy and fusion with interbody cage and plating was performed 6–12 h after traction positioning. Most patients (19, 86%) had spinal cord injury: 7 were Frankel A (31%), 3 Frankel B (14%), 6 Frankel C (27%), 3 Frankel D (14%), and 3 Frankel E (14%). No neurologic deterioration was observed after the treatment. In 10 cases (45%), neurological symptoms improved 1 year after the trauma. Two patients (10%) died for complication related to spinal cord transition or other organ damage. Conclusions: Early reduction gives the best chance of recovery for patients affected by C-type subaxial cervical fracture. Rapid traction is more often successful and safer than manipulation under anesthesia. After close reduction achieving, anterior microdiscectomy, cage, and plating implant seem to be safe and effective with a low rate of complications.